2014
DOI: 10.1016/j.molcel.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Autophagy Receptors and Ubiquitin-like Proteins Form the Molecular Basis for Selective Autophagy

Abstract: Selective autophagy ensures recognition and removal of various cytosolic cargoes. Hence, aggregated proteins, damaged organelles, or pathogens are enclosed into the double-membrane vesicle, the autophagosome, and delivered to the lysosome for degradation. This process is mediated by selective autophagy receptors, such as p62/SQSTM1. These proteins recognize autophagic cargo and, via binding to small ubiquitin-like modifiers (UBLs)--Atg8/LC3/GABARAPs and ATG5--mediate formation of selective autophagosomes. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
838
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 894 publications
(863 citation statements)
references
References 84 publications
11
838
1
13
Order By: Relevance
“…This protein is incorporated into mature autophagosomes and degraded in autolysosomes, serving as a readout of the autophagic pathway. 29 The distribution of SQSTM1/p62 puncta perfectly matches that of LC3 puncta ( Supplementary Figures S1c and d). Its transcriptional upregulation in Pat#1 fibroblasts further demonstrates that 13514A4G cells have an increased autophagosome formation rather than a block in their degradation (Figure 1d).…”
Section: Resultssupporting
confidence: 58%
“…This protein is incorporated into mature autophagosomes and degraded in autolysosomes, serving as a readout of the autophagic pathway. 29 The distribution of SQSTM1/p62 puncta perfectly matches that of LC3 puncta ( Supplementary Figures S1c and d). Its transcriptional upregulation in Pat#1 fibroblasts further demonstrates that 13514A4G cells have an increased autophagosome formation rather than a block in their degradation (Figure 1d).…”
Section: Resultssupporting
confidence: 58%
“…As a result, autophagy cargo receptors act as molecular bridges that capture ubiquitylated proteins targeted for degradation by the autophagy pathway and complement the UPS. For example, the autophagy cargo receptors p62 (also known as SQSTM1), NBR1 (next to BRCA1 gene 1 protein) and histone deacetylase 6 (HDAC6) all promote the autophagic clearance of protein aggregates in a process known as aggrephagy, which is dependent on both the UBD and LIR 2,10 . In yeast, although orthologues of UBD-containing adaptor proteins such as p62 are missing, a recent mass spectrometric study identified Cue5 as a potential autophagy cargo receptor 23 .…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
“…50 Although in general autophagy is an in bulk process, it can also be highly selective toward cellular structures and microorganisms invading the cytoplasm. The paradigm for selective autophagy is the recognition of the cargo by autophagy receptors (p62/SQSTM1, NBR1, NDP52, optineurin and BNIP3L), which connect the cargo to the autophagy machinery (reviewed in references Birgisdottir et al 51 ; Okamoto 52 ; Rogov et al 53 ; and Stolz et al 54 ).…”
Section: Autophagy and Ciliummentioning
confidence: 99%